Banking Business Innovations: Conceptual Foundations of Modern Economy Development - Yeremenko, Igor; Rudskaya, Elena (International Journal of Economics and Financial Issues, 2016)
The objective of the paper is to give scientific grounds for theoretical and methodological provisions of the digital banking concept as the most important trend of banking innovations. During the research, the general scientific cognition methods were used: analysis, generalization, modeling, abstraction, logical method as well as the systemic, institutional and evolutionary approaches. As a result of the study, the most important innovation processes in the sphere of banking service were revealed that reflect the innovative nature of development of the modern economy. The concluding stage is providing grounds for suggestions in forming the ecosystem of mobile payments for a commercial bank. Keywords: Innovation economy; banking innovations; digital banking platform; mobile banking; omni-channel. JEL Classification: G2